Intestinal Epithelial Cell Endoplasmic Reticulum Stress and Inflammatory Bowel Disease Pathogenesis: An Update Review - Ma, Xiaoshi; Dai, Zhaolai; Sun, Kaiji; Zhang, Yunchang; Chen, Jingqing; Yang, Ying; Tso, Patrick; Wu, Guoyao; Wu, Zhenlong (Frontiers in Immunology, 2017)
The intestinal epithelial cells serve essential roles in maintaining intestinal homeostasis, which relies on an appropriate endoplasmic reticulum (ER) function for proper protein folding, modification, and secretion. Exogenous or endogenous factors with ability to disturb the ER function impair the intestinal barrier function and activate inflammatory responses in the host. The last decade has witnessed considerable progress in the understanding of the functional role of ER stress and unfolded protein response (UPR) in the gut homeostasis and its significant contribution to the pathogenesis of inflammatory bowel disease (IBD). Herein, we review recent evidence supporting the viewpoint that deregulation of ER stress and UPR signaling in the intestinal epithelium, including the absorptive cells, Paneth cells, goblet cells, and enteroendocrine cells, is implicated in genetic or environmental factors driving colitis in experimental animals and IBD patients. In addition, we highlight pharmacologic application of chaperones or small molecules that enhance protein folding and modification capacity or improve the function of the ER. These molecules represent potential therapeutic strategies in the prevention or treatment of IBD through restoring ER homeostasis in intestinal epithelial cells.